Stakeholders’ viewpoints analysis on mobility as a service using the MAMCA and the fuzzy AHP method - Willy Kriswardhana; Domokos Esztergár-Kiss (Journal of Urban Mobility)
Mobility as a Service (MaaS) is not a new mobility concept, yet its implementation is still limited. While the demand for MaaS has been widely explored, the key stakeholders’ viewpoints have not been extensively investigated yet. The benefits of the service can be materialized once stakeholders’ expectations are identified. Therefore, current study performs a quantitative analysis based on a survey among MaaS-related stakeholders where Fuzzy Analytic Hierarchy Process is used to assess the importance of their objectives and criteria. The results show that the users expect lower travel costs when using MaaS. Common important objectives and criteria are found for public transport and private operators, especially in terms of supporting multimodal trips. However, while public transport operators consider relevant social impacts, such as increased customer satisfaction, and multimodal integration, private operators prioritize business impacts, such as gaining more customers and higher market share. MaaS operators are interested in reaching agreements with several transport operators and provide a reliable user-centric mobility platform. Finally, the legislators expect MaaS to help lower the environmental impacts of transportation, such as air pollution. Thus, integrated solutions involving close cooperation between actors considering their perspectives should be created to support the future MaaS implementation.